The Difference of Lens Thickness in Acute and Chronic Primary Angle Closure Glaucoma - Sucyeka Syafutri; Fitratul Ilahi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Lens thickness is one of the factors that influence the mechanism of acute primary angle closure glaucoma (PACG). The thicker lens usually results in a shallower anterior chamber angle (ACA), and the gradual and progressive increase in lens thickness with age results in exaggerated shallowing of the ACA. Because lens thickness has an important role in acute PACG mechanism, prophylactic treatment like lens extraction might prevent PACG in early stages. This study aimed to describe the difference in lens thickness in acute and chronic PACG. Methods: The research was a cross-sectional study with samples conducted in Dr. M. Djamil General Hospital from September-December 2019. The number of eyes that fulfilled the inclusion criteria were 50 eyes from 50 patients consisting of 25 eyes with acute PACG and 25 eyes with chronic PACG. Subjects were examined with ocular biometry using A-scan biometry to evaluate lens thickness. Data were processed and analyzed using a computer program with a chi-square test. Results: Mean of lens thickness in acute PACG is 5.02 ± 0.45, while in chronic PACG is 4.86 ± 0.40. The difference in lens thickness in acute and chronic PACG were statistically significant (p = 0,037). Conclusion: Lens thickness is thicker in acute PACG than in chronic PACG.